LP‐003, a novel high‐affinity anti‐IgE antibody for inadequately controlled seasonal allergic rhinitis: A multicenter, randomized, double‐blind, placebo‐controlled phase 2 clinical trial - Kai Guan; Shuang Liu; Yan Feng; Lisha Li; Xiaoming Zhu; Nai‐Chau‐Sun Bill; Haili Ma; Jie Yang; Cuicui Han; Heng Liu; Qingyu Wei; Haiyun Shi; et al. (Clinical and Translational Allergy)
Abstract Background Anti‐IgE therapy can serve as an option for inadequately controlled seasonal allergic rhinitis (SAR) patients. LP‐003, a novel anti‐IgE antibody, is being tested as an add‐on treatment for SAR. This trial aimed to evaluate whether LP‐003 is effective and safe for SAR. Methods This placebo‐controlled double‐blind phase 2 randomized clinical trial was conducted in 17 hospitals in China. SAR patients whose symptoms were inadequately controlled despite first‐line treatment (nasal corticosteroids with or without oral antihistamine) in the previous two seasons were enrolled between July 6, 2023 and August 7, 2023. Participants were randomized in a ratio of 2:4:3 to receive subcutaneous injections of 100 mg LP‐003, 200 mg LP‐003 or placebo every 4 weeks for 2 doses. All patients received fluticasone propionate as standard‐of‐care (SoC). The main outcome was the mean total nasal symptom score (TNSS) during the peak pollen period (PPP). Secondary endpoints included a series of symptom and medication scores, quality of life assessments during PPP and pollen period (PP), immunogenicity and safety. Results A total of 180 participants were randomly assigned. The LP‐003 + SoC treatment achieved a significantly lower TNSS compared with placebo + SoC (3.31 vs. 4.06, intergroup difference = −0.74, p = 0.0464). For key secondary outcomes, the LP‐003 group also achieved significantly lower daily nasal symptom and rescue medication use scores (3.54 vs. 4.42, intergroup difference = −0.88, p = 0.0352), and daily ocular symptom and rescue medication use scores (1.66 vs. 2.19, intergroup difference = −0.54, p = 0.0245) compared to the placebo group. The suppression of free IgE was prevalent and persistent. There was no statistically significant difference in adverse events and severe adverse events between LP‐003 and placebo groups. Conclusions These findings support LP‐003 as a promising add‐on option to the SoC for patients with moderate to severe SAR. Fixed dosage regimen and extensive suppression of free‐IgE render it a cutting‐edge advantage.